Analisis Produktivitas Pegawai terhadap Pelayanan Permasalahan Kinerja Aparatur Sipil Negara di Direktorat Status Kedudukan Kepegawaian Kantor Pusat Badan Kepegawaian Negara (BKN) Jakarta - Dede Ipan; Darmeinis Darmeinis (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to analyze the performance of human resources in the Directorate of Civil Service Status at the State Civil Service Agency in handling service problems or ASN status cases. Labor productivity is influenced by various factors related to the workforce itself as well as those related to the company environment and government policies as a whole, such as education, skills, discipline, attitude and work ethics. Research methods are classified based on the objectives and level of natural setting of the object, research methods can be classified into basic research objectives, applied research methods and research and development. In this study, the researcher chose the type of Qualitative research to present and describe in detail and in detail the analysis of employee productivity in serving ASN performance problems at the Directorate of Civil Service Status of the BKN. Research Results Overall, the quality of service at the Directorate of Civil Service Status of the State Civil Service Agency (BKN) can be categorized as very good, supported by clarity of information, ease of access through various communication channels, and employee responsiveness in handling complaints. The completeness of the files submitted by the proposing agency greatly affects the speed of the service process. When the files are complete, the process can run quickly and efficiently. However, incomplete files are often the cause of delays in service. and the use of technology, such as the ASN SI application, is very helpful in improving the efficiency and effectiveness of services. Technology allows ASN to access information and services more quickly and easily.